Monolithic Two-Terminal Tandem Solar Cells Using Sb2S3 and Solution-Processed PbS Quantum Dots Achieving an Open-Circuit Potential beyond 1.1 V - Kern, Selina; Yi, Gyusang; Büttner, Pascal; Scheler, Florian; Tran, Minh Hoa; Korenko, Sofia; Dehm, Katharina; Kundrata, Ivan; Zahl, Achim; Albrecht, Steve; Bachmann, Julien; Crisp, Ryan (ACS Applied Materials and Interfaces, 2024)
Multijunction solar cells have the prospect of a greater theoretical efficiency limit than single-junction solar cells by minimizing the transmissive and thermalization losses a single absorber material has. In solar cell applications, Sb2S3 is considered an attractive absorber due to its elemental abundance, stability, and high absorption coefficient in the visible range of the solar spectrum, yet with a band gap of 1.7 eV, it is transmissive for near-IR and IR photons. Using it as the top cell (the cell where light is first incident) in a two-terminal tandem architecture in combination with a bottom cell (the cell where light arrives second) of PbS quantum dots (QDs), which have an adjustable band gap suitable for absorbing longer wavelengths, is a promising approach to harvest the solar spectrum more effectively. In this work, these two subcells are monolithically fabricated and connected in series by a poly(3,4-ethylene-dioxythiophene) polystyrene sulfonate (PEDOT:PSS)-ZnO tunnel junction as the recombination layer. We explore the surface morphology of ZnO QD films with different spin-coating conditions, which serve as the PbS QD cell’s electron transport material. Furthermore, we examine the differences in photogenerated current upon varying the PbS QD absorber layer thickness and the electrical and optical characteristics of the tandem with respect to the stand-alone reference cells. This tandem architecture demonstrates an extended spectral response into the IR with an open-circuit potential exceeding 1.1 V and a power conversion efficiency of 5.6%, which is greater than that of each single-junction cell.
CRIS-Team Scopus Importer:2024-03-29
Keywords: antimony sulfide; atomic layer deposition; chalcogenide solar cells; lead sulfide; mapping ellipsometry; multijunction; nanocrystals; recombination layer

Solid state interdigitated Sb(2)S(3)based TiO(2)nanotube solar cells - Büttner, Pascal; Döhler, Dirk; Korenko, Sofia; Moehrlein, Sebastian; Bochmann, Sebastian; Vogel, Nicolas; Minguez-Bacho, Ignacio; Bachmann, Julien (RSC Advances, 2020)
TiO(2)nanotubes generated by anodization of metallic titanium sputter-coated on indium tin oxide (ITO) substrates are used as a conductive scaffold for all solid-state Sb2S3-sensitized extremely thin absorber (ETA) solar cells. A blocking layer of TiO(2)placed between Ti and ITO in combination with optimized Ti deposition and anodization conditions enables the formation of crack-free layers of straight, cylindrical TiO(2)nanotubes of tunable length and diameter. ALD (atomic layer deposition) is subsequently used to coat this substrate conformally with a highly pure Sb(2)S(3)light absorber layer under an inert atmosphere. The high absorption coefficient of Sb(2)S(3)as compared to molecular dyes allows for the utilization of very short nanotubes, which facilitates the infiltration of the organic hole transport material and formation of a p-i-n heterojunction in an interdigitated and tunable geometry. We investigate the influence of nanotube length and of the absorber thickness to enhance the photocurrent value to twice that of planar reference structures.
CRIS-Team WoS Importer:2020-08-28

Solid state interdigitated Sb(2)S(3)based TiO(2)nanotube solar cells - Büttner, Pascal; Döhler, Dirk; Korenko, Sofia; Möhrlein, Sebastian; Bochmann, Sebastian; Vogel, Nicolas; Minguez Bacho, Ignacio; Bachmann, Julien (RSC Advances, 2020)
TiO(2)nanotubes generated by anodization of metallic titanium sputter-coated on indium tin oxide (ITO) substrates are used as a conductive scaffold for all solid-state Sb2S3-sensitized extremely thin absorber (ETA) solar cells. A blocking layer of TiO(2)placed between Ti and ITO in combination with optimized Ti deposition and anodization conditions enables the formation of crack-free layers of straight, cylindrical TiO(2)nanotubes of tunable length and diameter. ALD (atomic layer deposition) is subsequently used to coat this substrate conformally with a highly pure Sb(2)S(3)light absorber layer under an inert atmosphere. The high absorption coefficient of Sb(2)S(3)as compared to molecular dyes allows for the utilization of very short nanotubes, which facilitates the infiltration of the organic hole transport material and formation of a p-i-n heterojunction in an interdigitated and tunable geometry. We investigate the influence of nanotube length and of the absorber thickness to enhance the photocurrent value to twice that of planar reference structures.